Perception Forms of Profession and Expactations for The Future of Nurses and Midwifes - Feride Taşkın Yılmaz; Hanife Tiryaki Şen; Fatma Demirkaya (Association of Nurse Managers, 2015)
OBJECTIVE: The study was carried out in order to determine perception forms of profession and expactations for the future of nurses and midwifes. METHODS: The study which was carried out descriptive included 940 nurses and midwifes. Definition form and questionnaire form which included perception forms of profession and expectations for the future were used as data collecting tools. Datas were analized average, percentage and chi-square test. RESULTS: 73.2% of participants were nurses and 26.8% of participants were midwifes. It was determined that 64.7% of nurses and 69% of midwifes worked in their profession fondly, 23.5% of nurses and 20.2% of midwifes thought that status of their professions was high. In the study, it was established that aspects of the future of 37.6% of nurses and 36.5% of midwifes were negative in terms of profession and 38.1% of nurses and 32.5% of midwifes thought that status of profession would be better in the future. CONCLUSION: It was determined that perceptions of profession of nurses and midwifes were not good levels although they worked in their professions fondly, nurses and midwifes perceived profession almost the same and expactations for the future of nurses and midwifes were partly positive.